Comparison between photostimulable phosphor plates using one or two angulations and cone beam computed tomography scans in detecting root fracture in endodontically treated teeth - Boulos Bechara; Sabika El Muraikhi; Alex McMahan; Ibrahim Nasseh; Maria Moarbes; Sayde Sokhn; Marcel Noujeim (Wolters Kluwer Medknow Publications, 2015)
Objectives: Artifacts due to the Gutta-percha may result in an incorrect diagnosis when using cone-beam computed tomography (CBCT) only. Compare CBCT scans with photostimulable phosphor (PSP) plates using one angulation and PSP plates using two different angulations in detecting root fractures (RFs) in endodontically treated teeth. Materials and Methods: Sixty-six roots were collected and treated endodontically using gutta-percha. One-half of the roots were randomly selected and fractured. 8 cm × 8 cm fields of view (FOV) were acquired with a CBCT machine. Periapical radiographs (using intra-oral PSP plates) were also acquired using one and two angulations. Results: The area under the receiver operating characteristic curve and sensitivity were significantly greater using CBCT than using one or two PSP plate angulations. There were no significant differences between one or two PSP plate angulations. Conclusion: The accuracy of RF depiction in endodontically treated teeth using 8 cm × 8 cm FOV CBCT was greater than that obtained using one or two PSP plate angulations.